Association between double-leg squat and single-leg squat performance and injury incidence among incoming NCAA Division I athletes: A prospective cohort study. (November 2018) - Eckard, Timothy; Padua, Darin; Mauntel, Timothy; Frank, Barnett; Pietrosimone, Laura; Begalle, Rebecca; Goto, Shiho; Clark, Michael; Kucera, Kristen
Abstract: Objectives: Determine the association between performance on the double-leg squat (DLS) and single-leg squat (SLS) and prospective injury incidence in athletes. Design: Prospective cohort study. Setting: National Collegiate Athletic Association (NCAA) Division I university. Participants: 111 incoming NCAA Division I athletes from 10 varsity sports teams. Main outcome measures: Performance on the DLS and SLS were assessed as "poor" or "non-poor." Lower extremity (LE) injury data for the following year were extracted from electronic medical records. Multivariate Poisson regression was used to compare the incidence of LE injuries in athletes with poor versus non-poor performance on the DLS and SLS. Results: The final models for the DLS and SLS were adjusted for sex and LE injury history and yielded an incidence rate ratio (IRR) of 1.33 (95% CI: 0.80 2.22) for the DLS and 1.62 (95% CI: 0.98, 2.66) for the SLS when comparing poor to non-poor movers. Conclusions: Athletes with poor LE movement quality assessed on the DLS or SLS had greater incidence of LE injury than those with non-poor movement quality. This is the first study to demonstrate an association between performance on the double-leg squat and single-leg squat and injury risk in NCAA athletes. Highlights: Novel double- and single-leg squat tasks have been developed to screen athletes. Scores on these tasks are meaningfully associated with lower extremity injury risk. Continued development of these screening tools is recommended in larger samples.